Securing Data in Wireless Body Area Network Using Hyper-Chaotic Zhou System - Hasan, Hasan Falah (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
E-Health care system is one of the great technology enhancements via using medical devices through sensors worn or implanted in the patient's body. Wireless Body Area Network (WBAN) offers astonishing help through wireless transmission of patient's data using agreed distance in which it keeps patient's status always controlled by regular transmitting of vital data indications to the receiver. Security and privacy is a major concern in terms of data sent from WBAN and biological sensors. Several algorithms have been proposed through many hypotheses in order to find optimum solutions. In this paper, an encrypting algorithm has been proposed via using hyper-chaotic Zhou system where it provides high security, privacy, efficiency and capacity in terms of long key space that ensures high resistance possibly obtained by any threat attack, key sensitivity is too high to any slight of change could be made in the encryption key and finally good statistical characteristic's analysis where the software has been used is microsoft visual studio version 10